PANCASILA SEBAGAI ETIKA POLITIK DAN HUKUM NEGARA INDONESIA [Pancasila as Political Ethics and Indonesian State Law] - Thomas Tokan Pureklolon (Fakultas Hukum, Universitas Pelita Harapan | Lippo Karawaci, Tangerang, 2020)
AbstractPancasila is not only a source of derivation of legislation, but also a source of morality, especially in relation to the legitimacy of power, law and various policies in the implementation and administration of the state. The existence of the first precept of